2004
DOI: 10.1111/j.1462-8902.2004.0349.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effect of diasulin, a herbal drug, on blood glucose, plasma insulin and hepatic enzymes of glucose metabolism in hyperglycaemic rats

Abstract: The present investigation suggests that diasulin, a polyherbal drug, controls the blood glucose level by increasing glycolysis and decreasing gluconeogenesis with a lower demand of pancreatic insulin than in untreated rats. This is possible, because it regulates the activities of hepatic glucose metabolic enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…4). Decreased fasting glucose could improve the body weight in diabetic rats, and this is consistent with other studies (Pari & Saravanan 2004, Nagarajan et al 2005. Another possible mechanism of the antidiabetic activity of G. alata, in addition to improving insulin secretion, is by delayed glucose absorption.…”
Section: Day 15supporting
confidence: 80%
“…4). Decreased fasting glucose could improve the body weight in diabetic rats, and this is consistent with other studies (Pari & Saravanan 2004, Nagarajan et al 2005. Another possible mechanism of the antidiabetic activity of G. alata, in addition to improving insulin secretion, is by delayed glucose absorption.…”
Section: Day 15supporting
confidence: 80%
“…Several workers have shown that hyperglycemia and hyperlipidemia are the common characteristics of alloxan-induced diabetes mellitus in experimental animals (Pari and Saravanan, 2004;Qiong et al, 2004;Umesh et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Many oral antihyperglycemic agents have significant side effects and some are ineffective in chronic diabetic patients [4]. In spite of the introduction of hypoglycemic drugs, diabetes and related complications continue to be a major medical problem [5].…”
Section: Introductionmentioning
confidence: 99%